Characterization of Humic Substance Extracted from Andisols, Spodosols, Peat, and Lignite - Eka Rahmi; Suwardi Suwardi; Basuki Sumawinata (Universitas Sebelas Maret, 2018)
Soil and other materials with high C-organic content are potential natural sources of humic substances. Until now the differences in the characteristics of such humic substances that are extracted from different sources have not been widely studied. Thus, this study was aimed to characterize humic substances extracted from andisols, spodosols, peat, and lignite. The highest C-organic (48.8%) and N (7.6%) were obtained from peat and spodosols, respectively. The andisols humic substance produced the highest total acidity (6.52 cmol kg-1). Humic substance extracted from spodosols was a mostly aliphatic group and phenolate –OH, while that of andisols and lignite contained more aromatic group and phenolate –OH, whereas the humic substance from peat was a predominantly aliphatic group and –COOH. The surface morphology of the humic substances observed using SEM showed varying densities and shapes due to differences in their respective degree of decomposition and the formation process involved. There has been significant interest in investigating the different characteristics of the humic substance. The type humic substances are important to be known considering of their positive effects on soil fertility and plant growth and development.